The History of a Legislative Proposal - Edward J. Larson (Educational Considerations, 1989)
Mostly through the efforts of local school administrators mobilized by AASA legislators became familiar and comfortable with LEAD during the Spring and Summer of 1984. (Development and Implementation of LEAD)